PENGARUH ANEMIA IBU HAMIL TERHADAP BERAT BAYI LAHIR RENDAH: STUDI META ANALISIS BEBERAPA NEGARA TAHUN 2015 HINGGA 2019 - Aditianti Aditianti; Sri Poedji Hastoety Djaiman (IAKMI South Tangerang Branch, 2020)
Abstract Background: The prevalence of low birth weight (LBW) in Indonesia shows a decrease, but the risk factor for anemia in pregnant women has increased sharply and this has an impact on increasing the prevalence of LBW. Objective: This study aimed to determine the risk of anemia in pregnant women to the prevalence of LBW in several countries. Methods: This study was a meta-analysis using PRISMA. Eleven of the 122,000 studies met criteria for the analysis. Presentation of the data used a forest plot with a random effect statistical model. Results: The combined odds ratio (OR) showed that the effect of anemia in pregnant women on LBW was 1.49 times higher than that of non-anemia mothers (95% CI: 1.26-4.60; p <0.001). The variance was 53,7%. The results of the funnel plots from 11 studies were not evenly distributed so that the information obtained was homogeneous, focusing more on the middle value. Conclusion: There was an effect of anemia in pregnant women with the prevalence of LBW. Detection of anemia in pregnant women needs to be done as early as possible by involving the role of health workers and cadres. Outreach activities for young women at schools and Posyandu must be carried out regularly and continuously. Keywords: Anemia, LBW, Pregnancy Abstrak Latar belakang: Prevalensi berat bayi lahir rendah (BBLR ) di Indonesia menunjukkan penurunan namun faktor risiko anemia pada ibu hamil meningkat tajam dan hal ini berdampak pada peningkatan kejadian BBLR. Tujuan: Studi ini bertujuan untuk mengetahui besarnya risiko ibu hamil anemia terhadap kejadian BBLR di beberapa negara. Metode: Studi ini merupakan meta analisis menggunakan PRISMA. Sebelas dari 122.000 studi masuk dalam kriteria untuk dianalisis. Penyajian data menggunakan forest plot dengan model statistik random effect. Hasil: Besar odds ratio (OR) gabungan menunjukkan bahwa pengaruh ibu hamil anemia terhadap BBLR 1,49 kali lebih tinggi dibandingkan ibu yang tidak anemia (95%CI: 1,26-4,60; p<0,001). Besarnya varian 53,7 persen. Hasil funnel plot dari 11 studi ini tidak tersebar secara merata sehingga informasi yang diperoleh homogen, lebih fokus pada nilai tengah. Kesimpulan: Terdapat pengaruh anemia pada ibu hamil dengan kejadian BBLR. Deteksi anemia pada ibu hamil perlu dilakukan sedini mungkin dengan melibatkan peran tenaga keseharan dan kader. Penyuluhan bagi remaja putri di sekolah dan posyandu harus dilakukan secara berkala dan berkesinambungan Kata kunci: Anemia, BBLR, Kehamilan